Pola Asuh Orangtua Pengganti Pada Pembentukan Akhlak Anak - Fitriatul Umami; Hanik Mufaridah (Fakultas Dakwah Universitas Ibrahimy, 2022)
Parenting is a form of education that is applied in everyday life for children and of course every family has a different way or form of education which is motivated by education and past experiences. The purpose of this study was to describe the parenting style of substitute parents in the formation of children’s morals. The research method used is a qualitative research method with a case study research model. The results showed that the parenting style applied by substitute parents in Sumenep was permissive (elabung) and democratic (diejepe) parenting. Permissive parenting (sheath) with the characteristics of giving freedom to children by accepting, understanding, behavior and actions of children. While democratic parenting (diejepe) that parents provide guidance, attention, and direction. Furthermore, the moral formation of the three informants towards God, parents, teachers and friends that the morals they have, namely the first informant (RM) and the second (MA) have poor morals. While the third informant (MAP) has a commendable character